Radiation attenuation effectiveness of the inverse freezing fluid - a new shielding material for gamma radiation - Reshma Karunakaran; Rajagopal Shanmugasundaram (Discover Applied Sciences)
Abstract The inverse freezing fluids are the new field of science, in which the synthesised fluid mixtures freezes at high temperature and liquifies at lower temperature. Recently we observed such a new thermal and thermal–mechanical metamaterial behaviour from the liquid mixtures of citric acid and ethanolamine solution under different conditions. This new science is still in the basic research stage with no applications so far developed. This is the first paper which gives a detailed description about the application of such inverse freezing fluids. Here we have opted to study the gamma radiation shielding of the synthesised inverse freezing fluids (IFF) namely, pure IFF and metals such as, vanadium and molybdenum doped IFF samples. From the data reported and analysis in this manuscript, it is evident that different liquids mixtures, especially, IFF’s can be used for gamma radiation shielding with varying temperature. We found better shielding parameters while taking IFF’s at higher temperature. The effect of temperature has influenced the radiation absorption and transmittance through the samples. Comparison plots were given for better understanding with which the molybdenum doped sample shows better shielding than the other two samples. In case of the Co-60 source the absorption factor is 0.3418, LAC is 1.1396 cm−1 and MFP was 0.8774 cm−1 for molybdenum doped samples which are evidently more compared to the vanadium doped samples. To the best of our knowledge this is the first comprehensive study exploring the temperature dependent gamma attenuation properties of the soft matter which is initially in the liquid form. Fundamental discovery of such IFF’s are promising research materials, in the context of emerging liquid phase systems for the radiation shielding applications.